DEVELOPMENT TRENDS OF DIGITAL MARKETING - Солнцев, Сергій Олексійович; Жигалкевич, Жанна Михайлівна; Залуцький, Руслан Олександрович (Journal of Strategic Economic Research, 2023)
The article studies the development trends of digital marketing based on the analysis of statistical data on the use of the Internet and social networks in 2020–2022. It has been established that the number of Internet users in the world and Ukraine, in particular, is growing rapidly. It is assumed that one of the levers for increasing Internet users was the outbreak of the COVID-19 pandemic and the quarantine restrictions associated with it. It is traced that the means of remote communication have also received rapid development. This led to the actualization of mass communication on the Internet, where social networks play a significant role. Social networks have become a platform for personal communication and a powerful tool for business development and product promotion. It is noted that thanks to the huge user base of networks such as Facebook and Instagram, advertisers can reach billions of potential customers. The role of artificial intelligence and machine learning as necessary tools for analyzing and processing large amounts of information is determined. Based on the analysis of social networks, the most popular applications were identified: Facebook, Telegram – as a platform for convenient and fast communication; Instagram, TikTok – as an opportunity to conveniently view media materials; Linkedin – as a communication channel between potential employees and employers; Twitter – as a platform for exchanging opinions with a wide public circle of people through text posts, etc. It has been established that the popularity of using social networks has become the basis for highlighting the most modern innovative approach to marketing management – influencer marketing. An examination of expert data on the top reasons people aged 16 to 64 use the Internet found that the majority of users utilize social media as a means of keeping in touch with family and friends and as a means of finding new products and exploring new brands. To improve the effectiveness of social media marketing, a list of recommendations is proposed. The conclusions highlight several main trends in digital marketing and substantiate the need for further research on the development methods for expanding adaptability to the innovative and technological challenges of the digital environment.